HDAC5 controls a hypothalamic STAT5b-TH axis, the sympathetic activation of ATP-consuming futile cycles and adult-onset obesity in male mice - Raian E. Contreras; Tim Gruber; Ismael González-García; Sonja C. Schriever; Meri De Angelis; Noemi Mallet; Miriam Bernecker; Beata Legutko; Dhiraj Kabra; Mathias Schmidt; Matthias H. Tschöp; Ruth Gutierrez-Aguilar; et al. (Elsevier, 2024)
With age, metabolic perturbations accumulate to elevate our obesity burden. While age-onset obesity is mostly driven by a sedentary lifestyle and high calorie intake, genetic and epigenetic factors also play a role. Among these, members of the large histone deacetylase (HDAC) family are of particular importance as key metabolic determinants for healthy ageing, or metabolic dysfunction. Here, we aimed to interrogate the role of class 2 family member HDAC5 in controlling systemic metabolism and age-related obesity under non-obesogenic conditions. Starting at 6 months of age, we observed adult-onset obesity in chow-fed male global HDAC5-KO mice, that was accompanied by marked reductions in adrenergic-stimulated ATP-consuming futile cycles, including BAT activity and UCP1 levels, WAT-lipolysis, skeletal muscle, WAT and liver futile creatine and calcium cycles, and ultimately energy expenditure. Female mice did not differ between genotypes. The lower peripheral sympathetic nervous system (SNS) activity in mature male KO mice was linked to higher dopaminergic neuronal activity within the dorsomedial arcuate nucleus (dmARC) and elevated hypothalamic dopamine levels. Mechanistically, we reveal that hypothalamic HDAC5 acts as co-repressor of STAT5b over the control of Tyrosine hydroxylase (TH) gene transactivation, which ultimately orchestrates the activity of dmARH dopaminergic neurons and energy metabolism in male mice under non-obesogenic conditions.